Binder Jetting 3D Printing of Titanium Aluminides Based Materials: A Feasibility Study; Advanced Engineering Materials; Vol. 22, iss. 9 - Yadav P. Pinku; Fu Z. Zongwen; Knorr M. Moritz; Travitsky (Travitzky) N. Nakhum (2020, 2020)
Title screen